Plasma, aqueous and vitreous homocysteine levels in proliferative diabetic retinopathy. Issue 5 (21st February 2012) - Lim, Chern Pin; Loo, Angela Voon Pei; Khaw, Keat Ween; Sthaneshwar, Pavai; Khang, Tsung Fei; Hassan, Mohd; Subrayan, Visvaraja
Abstract : Background/Aims: To compare homocysteine (Hcy) concentration in the blood plasma, vitreous and aqueous of eyes with proliferative diabetic retinopathy (PDR) against control, and to investigate associations between Hcy concentration in blood plasma with that of aqueous and vitreous in these two groups. Methods: Blood plasma, aqueous and vitreous samples were collected during combined cataract and pars plana vitrectomy from 20 eyes with PDR and 21 eyes of patients without diabetes mellitus. Hcy concentration in the samples was determined by chemiluminescent microparticle immunoassay. Results: The mean Hcy concentration (± standard deviation) of blood plasma, vitreous and aqueous were 13.7± 2.2 μmol/l, 3.4±0.7 μmol/l and 1.6±0.3 μmol/l respectively in the PDR group; in the control group, they were 10.4±1.1 μmol/l, 2.6±0.9 μmol/l and 1.2±0.2 μmol/l, respectively. The estimated geometric mean of Hcy concentration of all three variables in the PDR group was about 30% higher than control. In the PDR group, Hcy concentration between the blood plasma and vitreous was significantly associated (ρ=0.71; p-value < 0.001), as was that between the blood plasma and aqueous (ρ=0.68; p-value < 0.001). In the control group, only Hcy concentration in the blood plasma and vitreous was significantly associated (ρ=0.66; p-value = 0.001). Conclusion: The geometric mean of Hcy concentration in the blood plasma, vitreous and aqueous of the PDR group was significantly higher than control. The Hcy levels in the blood plasma and vitreous were also significantly associated in both groups. However, the blood plasma and aqueous were significantly associated only in the PDR group.